2014
DOI: 10.1186/1471-2393-14-281
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and incentives for achieving partograph use in obstetric practice in low- and middle-income countries: a systematic review

Abstract: BackgroundThe partograph is a graphic display of the progress of labour, recommended by the World Health Organization, but often underused in practice in low- and middle-income countries. We were interested in going beyond demonstration of potential efficacy – on which the existing literature concentrates - through a systematic review to identify barriers to and incentives for achieving partograph use.MethodsWe searched Ovid MEDLINE, Ovid Maternity and Infant Care, POPLINE, Web of Science, and Scopus, from 1st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 45 publications
3
69
1
1
Order By: Relevance
“…This implies that provision of enabling environment such as provision of partograph chart and observation tools may make the nurses /midwives to use the partograph if they are skilled as they implicated non availability of resources as determinant of their non-utilization of the partograph. This agreed with Ollerhead and Osrin [15] who included clinical leadership and quality assurance, as well as organizational environment as part of the barriers to use of partograph.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This implies that provision of enabling environment such as provision of partograph chart and observation tools may make the nurses /midwives to use the partograph if they are skilled as they implicated non availability of resources as determinant of their non-utilization of the partograph. This agreed with Ollerhead and Osrin [15] who included clinical leadership and quality assurance, as well as organizational environment as part of the barriers to use of partograph.…”
Section: Discussionsupporting
confidence: 62%
“…The same study found out that non -availability of partograph charts in labour wards and poor knowledge of the partograph were factors affecting its use. Ollerhead and Osri [15] included clinical leadership and quality assurance, as well as organizational environment as part of the barriers to use of partograph.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] A partograph is a graphic display of the progress of labour, which helps skilled birth attendants to recognise emerging difficulties and take action according to a clinical management protocol. 37 The overall health facility deliveries improved by 46% from a median of 110 to 161 deliveries per month in a collaborative of 23 health facilities from February 2010 to June 2011. The target was to achieve a median of 220 deliveries per month.…”
Section: Improving Newborn Survival In Southern Tanzania (Insist): Qimentioning
confidence: 99%
“…Overburdened health systems in Bangladesh are often unable to supply the administrative and organizational support needed for proper and consistent use of the partograph. Shortage of trained personnel 31 who are competent in labor management and inadequate referral systems for women in labor who experience complications are more evident in low resource countries. Moreover, the tool itself may present difficulties for health care providers as they lack the underlying knowledge and skills that is required for proper monitoring of the patient, drawing of the partograph with the findings and ultimately manual interpretation of data.…”
Section: Problem Description Of Use Of Paper Partographmentioning
confidence: 99%
“…Trainers and supervisors must recognize that, while the partograph appears to be simple, it assumes a foundation of knowledge and skills in assessment of labor, gathering of data, presentation and interpretation of data are also essential 31 . Every facility that serves laboring women must have clearly articulated protocols of care that is synchronized with the partograph.…”
Section: Problem Analysis and Justification Of New Toolsmentioning
confidence: 99%